Aktivitas Ekstrak Daun Kelor Terhadap Sel-T Helper dan Sel-T Sitotoksik pada Mencit yang Diinfeksi Salmonella thypi (ACTIVITY OF AQUEOUS LEAF EXTRACT OF HORSERADISH TREE ON HELPER T- CELL AND CYTOTOXIC T- CELL IN MICE INFECTED WITH SALMONELLA THYPI) - Fathir, Akhmad; Rifa’i, Muhaimin; ., Widodo (Jurnal Veteriner, 2014)
Typhoid fever is caused by Salmonella typhi infection, and it is a still problem in many developingcountries, including Indonesia. Typhoid fever occurs due to T cells, immune system, especially CD4+ andCD8+ T cells, are deficient. This condition can cause S. thypi infects human body cells . The study aim wasto evaluate profile CD4+ and CD8+ T cells in mice spleen (Mus musculus) infected with  S. thypi afterinducted with aqueous leaf extract of horseradish tree. An experimental laboratory studiy was conductedusing completely factorial randomized design. Mice were divided into two groups, ie non infection group(induced with aqueous leaf extract of horseradish tree, at dose 0 mg/kg BW, 14 mg/kg BW, 42 mg/kg BWand 84 mg/kg BW) and infection group, the Micewere infected with S. thypi (induced with aqueous leafextract of horseradish tree, at dose 0 mg/kg BW, 14 mg/kg BW, 42 mg/kg BW and 84 mg/kg BW). The resultshowed that aqueous leaf extract of horseradish tree increased the number CD4+  of and CD8+ T cells  in allgroups of mice in conclusion administration of aqueous leaf extract of horseradish tree at high dose havecauses immunosuppressive in immune system. Aqueous leaf extract of horseradish tree have aimmunostimulatory and immunosuppressive functions in CD4+ and CD8+ T cells.
Keywords: CD4+ T cell, CD8+ T cell, spleen, S. thypi, horseradish tree